Diagnostic performance of point-of-care ubiquitin carboxy-terminal Hydrolase-L1 assay in distinguishing imaging abnormalities in traumatic brain injury: A TRACK-TBI cohort study - Kevin K. Wang; Jennifer C. Munoz-Pareja; Lauren A. Lautenslager; J. Adrian Tyndall; Zhihui Yang; Maria R. Kerrigan; Ramon Diaz-Arrastia; Frederick K. Korley; David Okonkwo; Ava M. Puccio; John K. Yue; Sabrina R. Taylor; et al. (Advances in Biomarker Sciences and Technology, 2023)
The use of UCH-L1 detection with point-of-care (POC) assay alone has not been characterized for clinical use. This study compares the accuracies of POC UCH-L1 and Neuron-Specific Enolase (NSE) Elecsys® levels for identifying TBI patients with structural abnormalities on neuroimaging.The Transforming Research and Clinical Knowledge in Traumatic Brain Injury (TRACK-TBI) Phase 1 Cohort, enrolled 1375 TBI patients (GCS 3–15) presenting to one of 18 US Level I trauma centers within 24 h of injury who had an admission head CT; blood samples were collected, along with 122 orthopedic and 209 healthy controls. The TBI cohort consisted of 810 CT-negative (CT-) and 549 CT-positive (CT+) subjects. Of the CT- subjects who had MRIs, 121 were MRI-positive (MRI+) and 333 were MRI-negative (MRI-). UCH-L1 POC showed best diagnostic performance for CT + versus CT-, 0–8 h post-injury with an AUC of 0·779 [0·708–0.850] when compared to the 0–25 h interval, with an AUC of 0.684 [0.655–0.712]. NSE assay has an AUC of 0.695 [0.619–0.770] for the 0–8 h interval and 0.634 [0.603–0.665] for the 0–25 h interval. During the first 8 after injury, POC UCH-L1 outperforms NSE in identifying TBI patients with structural abnormalities on neuroimaging.